Nabokov, Dostoevski, Proust: Despair - Timothy L. Parrish (Studies in 20th & 21st Century Literature, 2004)
Although Nabokov criticism has long identified Despair with Dostoevski, critics have for the most part addressed Despair in terms of how it either attacks or validates Dostoevski and thus have understood Nabokov to be speaking primarily about Dostoevski's achievement as a novelist. As I argue, Despair revises Dostoevski as a sly assertion of Nabokov's paradoxical aesthetic independence, and does so through the medium of Marcel Proust. It predicts the more obvious Proustian influence that critics have noticed in Nabokov's later works. In Despair Proust gives Nabokov the fundamental modernist narrative that makes an artist's coming to consciousness coincident with the narrative the reader reads. Nabokov borrows Proust's narrative pattern and lends it to Hermann to mishandle, but neither author of Despair keeps it as his own. Despair is a failed Proustian novel, one that Nabokov arranges so that the failure is not technically his. Paying ironic and even humble tribute to the author to whom he was closest, Nabokov imprisons Hermann and his Dostoevskian fantasies within his own aesthetic universe and thereby separates Hermann's derivative Dostoevskian one from Nabokov's peculiarly original novel. Although Nabokov implies Proust is his ideal artist, the truth is that Nabokov, as always, points to himself. After Hermann disappears from the novel, one world remains, named Despair, and it belongs to Vladimir Nabokov and, perhaps, the reader.
Keywords: Nabokov; Despair; Dostoevski; Marcel Proust; Russian Literature; independence; Proustian influence; modernist narrative; modernist; ironic; irony; paying tribute; Hermann; Dostoevskian fantasies; Vladimir Nabokov